Kombinasi Colocasia esculenta L. dan Zingiber officinale Potensial Menghambat Inflamasi dan Nyeri - Ni Made Dwi Sandhiutami; Ali Timucin Atayoglu; Yati Sumiyati; Yesi Desmiaty; Rizky Adam Hidayat (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
The active metabolites of Colocasia esculenta L. and Zingiber officinale L. have been reported to reduce pain and exert anti-inflammatory effects. This study aimed to examine the anti-inflammatory and analgesic effects of a combination of C. esculenta and Z. officinale extract. Thirty rats and mice were each divided into 6 groups (n=5), namely the normal group, negative control, positive control (Nadiclofenac), and 3 test groups were given a extract combination (dose 1.3 mg/20 gBW, 2.6 mg/20 gBW, and 5.2 mg/20 gBW). Winter's method was used for anti-inflammatory tests by inducing carrageenan in rat paws, and Sigmund's method was used for analgesic tests by the intraperitoneal induction of acetic acid in mice. The percentage of inhibition of leg edema in rats was 11.33%, 18.90%, and 19.10% for the three doses of the combined extracts of C. esculenta and Z. officinale, and 22.72% for Na-diclofenac (p<0.05). The percentage inhibition in the analgesic test in the positive control group and the three test groups was 61.17%, 41.19%, 51.79%, and 52.35%, respectively (p<0.05). The combination of the C. esculenta and Z. officinale extracts exhibited anti-inflammatory and analgesic effects. Dose of 2.6 mg/20 gBW and 5.2 mg/20 gBW as effective as Na-diclofenac.